KEDUDUKAN KEPOLISIAN DALAM PENYIDIKAN TINDAK PIDANA KORUPSI MENURUT SISTEM PERADILAN PIDANA - Barhamudin, Barhamudin (Faculty of Law, University of Palembang, 2020)
This study aims to optimize the role of the police in investigating corruption in eradicating corruption in Indonesia. This legal research method is normative (normative research-legal). This study uses secondary data which includes primary, secondary and tertiary legal materials. Basic data includes human (legal) behavior both verbally and real behavior that has to do with law enforcement in eradicating criminal acts of corruption. The optimization of the role of the police in eradicating criminal acts of corruption is based on the concept of values ​​or basic ideas in the establishment of the Criminal Procedure Code which requires the realization of an integrated criminal justice system by carrying out professional investigations and meeting the demands of community justice by being non-selective and discriminatory. The realization of togetherness and harmony of relations between the components involved in the operation of an integrated criminal justice system in the settlement of corruption cases involving corruption, investigation and prosecution. Without the togetherness and harmony in the implementation of the authority to investigate criminal acts of corruption from the Police as a law enforcement agency that acts as an investigator of criminal acts of corruption in addition to the presence of the Public Prosecutor's Office, this will not play an optimal role.